Ocenjevanje samostojnosti odraslih slepih in slabovidnih - Kačič, Marino (Socialno delo, 2007)
People who in their adult life lose eyesight completely or to an extensive degree are usually assessed on the medical basis. The latter estimates theremaining sight and classifies a person as blind or visually impaired. Such assessment says nothing about individual''s capabilities or potentials, which is a central issue of the presented research; are these differences in the degree of independence between people who lost eyesight as adults, and if so, in which areas? To answer this question, a relevant measuring instrument had to be developed. The author devised a questionnaire (the REHA test for blind or visually impaired) about eight life areas thet are essentialfor the blind and visually impaired people''s independence. A pilot research performed on persons who attend seminars on rehabilitation and education has shown that the level of independencedepends on age, place of residence, acquired new skills, possession of technical aids, itc. The degree of the remaining sight does not always correspond with the degree of independence, which calls for assessment methods of a more complex nature. The presented questionnaire is capable of such assessment, It is a good basis for planning individualised help and personal counselling.
Keywords: slepi; slabovidni; vocational rehabilitation; rehabilitacija; samostojnost